DRAMA TARI ARJUNA WIWAHA KARYA S. MARIDI MAESTRO TARI TRADISI KARATON GAYA SURAKARTA SEBUAH KAJIAN ESTETIK - Sumargono, S., (Institut Seni Indoensia Surakarta, 2016)
This writting will disclose and identify the aesthetics of Arjuna Wiwaha dance by aplying a special attention to the analysis of dance’s elements and the relations of one element to the others. The notation patterns of the music of the dance were described in detail so that it was posible to identify the tempo,laya,rhythm,musical taste and the pattern of kendangan mungkus. The result is that we know the choreography of Arjuna Wiwaha dance has a harmonious impression. This aesthetic analysis was based on the aesthetic concept of Javanese traditional dancing of Surakarta style,both the techniqueand its taste. The concept covers pacak, pancat, lulut, luwes, ulat,wiled, rhythm and gendhing which are known as hastha sawanda. This writing at least can make a contribution to the aesthetic analysis on dance of Surakarta style and possibly other styles.Keywords: Arjuna Wiwaha, aesthetic, gendhing, dance movement, dramatic design.